Methods for evaluating the reliability of web portals at different stages of development using the integration of immutable infrastructure and containerization - Stepanov, Dmytro; Kruk, Oleh (Національний університет “Львівська політехніка”, 2025)
Summary. The article proposes a methodology for evaluating the dependability of web portals at various stages of their life cycle through the integration of Immutable Infrastructure and containerization technologies. As web systems grow in complexity and functional load, and as the demand for high availability and fault tolerance increases, traditional reliability assessment approaches based on defect density, error frequency, and test coverage become insufficient. The study substantiates the relevance of combining classical and modern reliability metrics within DevOps practices and CI/CD pipelines. Immutable Infrastructure entails the full replacement of system components during updates, eliminating configuration drift and ensuring environmental consistency. Containerization isolates software components, enhances execution repeatability, simplifies scalability, and improves recovery processes. Together, these technologies form the foundation for stable and predictable web portal performance under diverse operational conditions. The research systematizes key reliability indicators, including Mean Time Between Failures (MTBF), Mean Time To Recovery (MTTR), downtime duration, error frequency, defect density, test coverage, and cyclomatic complexity. The relevance of each metric is defined with respect to the corresponding development stage, from architectural design to deployment. The study also analyzes data collection and interpretation tools such as version control systems, automated testing frameworks, monitoring solutions, and orchestration platforms like Kubernetes and Docker. The use of SonarQube, Prometheus, and Terraform is examined in the context of automating reliability metric tracking and early risk detection. It is demonstrated that the proposed approach reduces recovery time by up to 15 %, decreases error frequency by up to 20 %, and enhances overall environment stability. The findings offer practical value to developers, testers, and DevOps engineers seeking to improve system dependability in compliance with ISO 4.2.5.2 (availability) and 4.2.5.4 (recoverability) standards. This scientific article is devoted to the development of a methodology for evaluating the reliability of web portals at different stages of their life cycle through the integration of immutable infrastructure and containerization technologies. With the growing complexity of web systems, increased functional load, and the need for high availability and fault tolerance, traditional approaches to reliability assessment—based primarily on test coverage, error rate, and defect density—are no longer sufficient. The article addresses this gap by proposing a structured framework for applying classical and modern reliability metrics in conjunction with DevOps and CI/CD practices. У статті запропоновано методологію оцінювання надійності веб-порталів на різних етапах їх життєвого циклу з використанням концепцій незмінної інфраструктури та контейнеризації. В умовах зростання складності веб-систем, збільшення функціонального навантаження і потреб у високій доступності та відмовостійкості, традиційні підходи, що базуються на оцінці дефектів, частоті помилок і тестовому покритті, втрачають ефективність. Обґрунтовано доцільність застосування поєднання класичних і сучасних метрик надійності у межах DevOps-підходів і CI/CDпрактик. Незмінна інфраструктура передбачає повну заміну компонентів системи під час оновлень, що усуває конфігураційний дрейф і забезпечує стабільність середовища. Контейнеризація забезпечує ізоляцію програмних компонентів, підвищує повторюваність виконання, спрощує масштабування та покращує процеси відновлення. Комбінація цих підходів створює передумови для стабільного функціонування веб-порталів у різноманітних операційних умовах. У роботі систематизовано ключові показники надійності: середній час міжвідмовної роботи, середній час відновлення, час простою, частоту помилок, щільність дефектів, покриття тестами та цикломатичну складність. Визначено релевантність кожної метрики для відповідного етапу життєвого циклу — від архітектурного проектування до впровадження. Також проаналізовано засоби збору та інтерпретації даних із використанням систем контролю версій, автоматизованого тестування, інструментів моніторингу та платформ оркестрування (Kubernetes, Docker). Представлено практики використання SonarQube, Prometheus і Terraform у контексті автоматизованого контролю метрик надійності та раннього виявлення ризиків. Показано, що запропонований підхід забезпечує зменшення часу відновлення (до 15%), зниження частоти помилок (до 20%) і підвищення стабільності середовищ. Отримані результати можуть бути використані розробниками, тестувальниками та DevOps-фахівцями для досягнення відповідності вимогам стандартів ISO 4.2.5.2 (доступність) та 4.2.5.4 (відновлюваність).
Методи оцінювання надійності веб-порталів на різних етапах розробки з використанням інтеграції незмінної інфраструктури та контейнеризації
Keywords: web portals, reliability assessment, immutable infrastructure, containerization, software development, methodologies, scalability, system management, веб портали, стабільність середовища; продуктивність системи; ефективність розгортання; час відновлення, доступність, відновлюваність, масштабованість; 004.415.5:004.451.86